Ensuring the Sustainable and High-Quality Development of Aquaculture Through Biosecurity: A Review and Prospects - Xuan DONG; Jie HUANG (Progress in Fishery Sciences)
This article reviews the importance of biosecurity in aquaculture and its role in promoting sustainable and high-quality development. As a strategic and comprehensive method based on risk analysis, the core objective of biosecurity is to prevent and control disease risks, which ensures the health and sustainable development of the industry. This article elaborates on the concept and historical development of biosecurity, distinguishing it from biosafety, disease prevention, aquaculture, and animal health while exploring the connections and differences between these concepts. The authors proposed that animal health needs three approaches, including biosecurity, animal welfare, and ecological intervention. Six elements for constructing a biosecurity system and implementing the biosecurity plan are identified. Subsequently, the article outlines the key scientific and technological issues involved in the biosecurity framework and introduces the current state of research and development in the fields of science, technology, and policy, both internationally and domestically. Furthermore, this article discusses the role of global and regional organizations in promoting aquaculture biosecurity strategies and the practices of different countries and regions in constructing aquaculture biosecurity regulatory systems. In particular, it introduces how international organizations such as the Food and Agriculture Organization of the United Nations (FAO) and the World Organization for Animal Health (WOAH) emphasize the application of the biosecurity concept to promote the sustainable development of aquaculture. This article also discusses the evaluation of biosecurity in aquaculture enterprises and its technical content. Using the cultivation of specific pathogen-free (SPF) shrimp seedlings as an example, this article introduces the development of biosecurity in international enterprises and the practices employed by the authors in shrimp hatcheries. Finally, this article highlights the challenges and opportunities for China in the field of aquaculture biosecurity and discusses the future direction of biosecurity strategies. This includes constructing a roadmap for the long-term development strategy of the national biosecurity plan; strengthening research, education, and awareness of biosecurity; prioritizing the development of biosecurity for the aquatic seed industry; and building an aquatic seed industry system with a high standard of biosecurity to ensure the sustainable and high-quality development of aquaculture industry in China.